The Cambridge-Cambridge Controversy in the Theory of Capital; A View from New Haven: A Review Article - Stiglitz, Joseph E. (Journal of Political Economy, 1974)
Economics has long been plagued with controversies: the Keynesian-monetarist controversy, the investment function controversy (is the elasticity of substitution unity?), the liquidity preference-loanable funds controversy. Geoffrey Harcourt has extended his survey article from the Journal of Economic Literature (1969) into a book dealing with one of the latest of these so-called controversies, that between Cambridge, England, and Cambridge, Massachusetts, concerning capital theory. The book is more balanced and more complete than the original survey article and includes some good pieces of exposition. The problems that I find with the book are basically problems I find with the Cambridge (U.K.) theory of which he is a partisan on one side-as, I suppose, I am on the other–and so, rather than focus on any errors and confusions which are peculiar to Harcourt, I prefer to focus on three of the major issues involved in the dispute and to suggest, in doing so, where Harcourt (and the Cambridge [U.K.] theorists) have gone astray.